Comparative statistical analysis of Turkish and European insurance sectors (based on the importance of insurance sectors in Turkish and European economies) - Karaoğlu, Senem (My University, 2007)
Bu çalışmanın amacı, Türkiye ve Avrupa ülkelerinin sigorta sektörlerinin karşılaştırmalı istatistiksel analizinin yapılması ve sigorta sektörünün ülkelerin ekonomilerine olan etkisinin görülmesidir.Bu amaçla altı tane değişken seçilmiştir ( Toplam prim üretimi, Toplam yurtiçi gelir, Toplam Yatırım, Şirket Sayısı, Toplam Nüfus, Enflasyon ve Toplam Çalışan Sayısı) ve bu değişkenlerin hem birbirleri ile hem de Toplam Prim Üretimi ile olan ilişkileri analiz edilmiştir.Tezin 1.Bölüm ve 2.Bölümlerinde sırasıyla Avrupa ve Türkiye Sigorta Sektörleri hakkında kısa bir bilgi verilmiştir. 3. Bölümde ise değişkenler tanımlanmış ve Regresyon, Cluster, One Way ANOVA ve Kruskal Wallis Testleri yardımı ile analizler yapılmıştır.Ülkelerin ekonomilerinin gelişimi ve sigorta sektörleri arasında güçlü bir ilişki olduğu saptanmıştır. Böylece Türkiye deki ekonomik gelişim daha çok insanın kendini sigorta yolu ile güvence altına almasını sağlamıştır fakat diğer taraftan Avrupalıların aksine Türk insanının sigortanın sağladığı sosyal, sağlık ve emeklilik hizmetlerinin tam olarak bilincinde olmadığı görülmüştür. COMPARATIVE STATISTICAL ANALYSIS OF TURKISH AND EUROPEAN INSURANCE SECTORS ( BASED ON THE IMPORTANCE OF INSURANCE SECTORS IN TURKISH AND EUROPEAN ECONOMIES)

of The Thesis Our main aim is in this study to evaluate Turkish and European Insurance sector based on importance of insurance sectors in Turkish and European Economies and also develop an objective of classification of countries (European countries and Turkey) as well as to compare and profile the structure of the Turkish and European Insurance sector. Second aim is to find out, the relationship between Total Premium Income (dependent variable) and GDP, Number of Employee, Inflation, Population, Number of Companies and investment. Part 1and Part 2 provide a literature review for the structure of European and Turkish insurance sector respectively. In part 3, we describe the variables which are used in the model and then use some statistical analyses to examine and classified the countries in the model. There is important relationship between insurance development and economic growth for developing countries. Thus, for example in Turkey economic growth allows societies to afford more insurance protection. However; large of the population is not fully aware of their social benefits, health care and pensions in Turkey contrast other European countries
Keywords: Sayısal Yöntemler; Sigorta ve Sigortacılık_Avrupa Ülkeleri_İstatistik; Sigorta ve Sigortacılık_Türkiye_İstatistik